(untitled) (Pedagogy of Higher and Secondary Education, 2022)
The traditional and other methodical techniques of effective nitftini. iifmn of educational activities of pupils at the music lesson at school, analyzed in the article. Gaining the experience of using these twchniques improves the professional Teachers Training activities of the future specialists.